Health Issues in The WTO Dispute Concerning Importation of Chicken Meat and Products between Indonesia and Brazil - Ari Siswanto (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
Article XX(b) of GATT justifies countries to adopt and apply trade measures to protect human health. It means that as long as the elements specified in Article XX(b) are satisfied, certain trade measures which infringe GATT rules and principles are permitted. Unfortunately, the rise of new protectionism and the unclear meaning of elements contained in Article XX(b) has likely attracted countries to use Article XX(b) as a pretext for enforcing protectionist trade measures. This research aims to address the meaning of elements of "necessary to protect human life or health" and "arbitrary or unjustifiable discrimination” as contained in Article XX(b) of GATT. It also provides an examination of how the elements have been interpreted and considered in the recent DS484 dispute involving Indonesia and Brazil over Indonesia’s trade measures concerning importation of chicken meat and product. This research, which is a normative legal research, adopted legal documents as the primary materials to be analyzed qualitatively. As the results, this research found that the element "necessary to protect human life or health" will likely be considered legitimate in a trade policy if the applying country can demonstrate the existence of health risks, take necessary measures to reduce these risks and there are no other alternative policies available that are more friendly towards international trade. As to the more subjective element of "arbitrary or unjustifiable discrimination", it can be concluded from the case examined that the principle of good faith had not yet been proportionally considered.